Actividad antibacteriana del extracto etanólico de pulpa de Couroupita guianensis Aubl. “ayahuma” frente a bacterias patógenas, Iquitos – Perú - Reátegui Cárdenas, Víctor Germán (2023)
In the Peruvian Amazon there are many plant species whose pharmacological properties are unknown, so in the present investigation the objective was to evaluate the antibacterial activity of the ethanolic extract of Couroupita guianensis Aubl "ayahuma" pulp. The fruits were collected in the town of San José - Ullpa caño, Itaya river. Phytochemical screening was performed by the modified method of Chhabra et al. and the antibacterial activity of the ethanolic pulp extract was measured by the Kirby-Bauer disk diffusion susceptibility test as well as the minimum inhibitory concentration (MIC) test against Klebsiella pneumoniae and Escherichia coli. Obtaining as results in the phytochemical screening of the extract the presence of saponins, phenols and tannins, steroids, lactone groups, essential oils and fats, and finally reducing compounds; in turn, this extract showed antibacterial activity against Klebsiella pneumoniae and Escherichia coli. Klebsiella pneumoniae showed greater sensitivity to the ethanolic extract of the pulp of Couroupita guianensis Aubl. at a concentration of 300 mg/mL and a MIC of 8 mg/mL; the two-way ANOVA shows us that in the interaction of the bacteria with the extract it shows a significant difference in contrast, the interaction between concentrations of the extracts against the bacteria showed that there is no significant difference, which is due to the fact that the range of concentrations is not very broad and biologically they express the same thing. Concluding that the ethanolic extract of the pulp of C. guianensis Aubl. it has good antibacterial activity against Klebisella pneumoniae and to a lesser extent against Escherichia coli; These activities are associated with the secondary metabolites found, mainly saponins, phenolic compounds, steroids, and lactone groups.